PERILAKU WIRAUSAHA PEDAGANG ETNIS CINA DI JALAN SAMANHUDI KABUPATEN JEMBER - Aini Nur Rohmah; Joko Widodo; Sutrisno Djaja (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2017)
This study aims to describe how the entrepreneur behavior of ethnic Chinese traders in Jalan Samanhudi Jember regency. Limited employment and increasingly intense competition among job seekers make some of people in Jalan Samanhudi Jember work as entrepreneurs. Formerly Jalan Samanhudi was one of Chinatown area in Jember Regency. Actually, there are many ethnic Chinese traders who trade in their shop. Through observations conducted by researchers they found that ethnic Chinese traders in Jalan Samanhudi Jember regency are able to maintain their business in a long time and quite successful in the field of trading although they are from the wandering people overseas. Those characteristics of entrepreneurial behavior shown by ethnic Chinese traders are not easy to despair, not to let go of opportunities, keeping promises, trying to convince customers during trading and have extremely good endurance and enthusiasm. Data collection methods used consisted of observation, interview and document methods. The analytical method used is descriptive qualitative. The result of this study indicate that the entrepreneur behavior of ethnic Chinese traders in Jalan Samanhudi Jember regency is very strong in running their business.